Hubungan Antara Dukungan Keluarga Dengan Gangguan Citra Tubuh Pada Penderita Kusta - Endang Mei Yunalia (Akademi Keperawatan Dharma Husada Kediri, 2017)
Leprosy is cronic disease caused by Mycobacterium leprae. Leprosy is not only physical disease but it also influence patien’s mental, social and economic. The purpose of this research was to identify the correlation between family support with body image disturbance on leprosy patients. This research is analytic correlation research wich used a cross sectional design. Sampling technique used purposive sampling and the sample consisted of 78 respondent. The result of this research most a half from respondent who has minimal family support have a negative body image (34,6%). Based on Contingency Coefficient test can get P-value 0,04< 0,05, with Coefficien Correlation 0,353, so H0 is refused and H1 accepted , it means that there is any correlation between family support with body image disturbance on leprosy patients. Based on the result of this research, its expected the family should be given a good support. Because with good family support patients can be motivated, so that patients receive the conditions that occur and not impaired body image. Key word: Leprosy, Body Image, Family Support